2021
DOI: 10.1038/s41380-021-01347-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of depression trait and state

Abstract: Major Depressive disorder (MDD) is a chronic and recurrent brain disorder characterized by episode and remission phases, and poor therapeutic responses. The molecular correlates of MDD have been investigated in case-control settings, but the biological changes associated with trait (regardless of episode/remission) or state (illness phases) remains largely unknown, hence preventing therapeutic opportunities. To address this gap, we generated transcriptome profiles in the subgenual anterior cingulate cortex of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…In our previous study, an immune function-related gene module associated with CRH+ cells showed the highest probabilistic association to MDD (16), suggesting a causal role of elevated immune response in CRH+ cells on the disease trajectory. It is unclear how these elevated immune response-and inflammation-related gene expression in CRH+ interneurons is associated with the pathophysiology of MDD.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In our previous study, an immune function-related gene module associated with CRH+ cells showed the highest probabilistic association to MDD (16), suggesting a causal role of elevated immune response in CRH+ cells on the disease trajectory. It is unclear how these elevated immune response-and inflammation-related gene expression in CRH+ interneurons is associated with the pathophysiology of MDD.…”
Section: Discussionmentioning
confidence: 80%
“…Recent animal and human studies implicate CRH and CRH+ cells in the stress response and trajectory of MDD across episode and remission phases (15,16,45), however, the molecular characteristics and pathological features of cortical CRH+ cells in the human brain are largely unknown. Here, we report that CRH is mostly expressed in GABAergic interneurons and that it overlaps with the major classes of interneurons in the human ACC, specifically VIP+ interneurons (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, insights into the transcriptional signatures associated with depressive traits and states have been made (Shukla et al, 2021 ). Using RNAseq from the anterior cingulate gyrus, Shukla and colleagues investigated transcriptional signatures from four different cohorts during: a first depressive episode; remission after the first episode; recurrent episodes, or remission after recurrent episodes.…”
Section: Sex-specific Molecular Alterations In Mddmentioning
confidence: 99%
“…Somatostatin-expressing (SST) GABAergic neurons can provide powerful inhibitions in both local and long-range brain networks [ 65 ]. Evidence suggests that somatostatin deficits are involved in depression pathophysiology [ 66 , 67 ]. MDD patients show reduced SST neurotransmission [ 68 ].…”
Section: Introductionmentioning
confidence: 99%